Relación entre el uso de redes sociales en internet y la ansiedad en adolescentes de una institución educativa de Hatonuevo.
The objective of this research was to describe the relationship between the use of social networks on the Internet and anxiety in adolescents from the Carlos Camargo Educational Institution in Hatonuevo, La Guajira. This study is based on a theoretical framework that explores the possible interactions between anxiety and behavior on social networks, a topic of relevance in youth mental health. The methodology was quantitative and used standardized instruments to evaluate the variables: the Social Network Addiction Questionnaire (ARS) to measure excessive use of networks, and the State-Trait Anxiety Inventory (IDARE) to measure anxiety levels, state and trait anxiety. The sample consisted of 50 adolescent students, who participated in the application of both questionnaires. The results suggest that, in general, there is no significant relationship between the anxiety dimensions and most aspects of social network use.